Blockchain Technology: Principles and Applications in Medical Imaging. - McBee, Morgan P.; Wilcox, Chad (Journal of Digital Imaging, 2020)
Blockchain is an immutable, encrypted, distributed ledger technology. While initially devised for and most commonly referenced with cryptocurrencies, there are an increasing number of applications outside finance, many of which are relevant to medical imaging. In this paper, the concepts and principles underlying the technology and applications relevant to medical imaging are discussed, in addition to potential challenges with implementations such as public versus private key access, distributed ledger size constraints, speed, complexity, and security pitfalls. Potential use cases for blockchain specifically relevant to medical imaging include image sharing including direct patient ownership of images, tracking of implanted medical devices, research, teleradiology, and artificial intelligence. While blockchain offers exciting ways to facilitate the storage and distribution of medical images, similar to the advent of picture archiving and communication systems decades ago, it does have several key limitations of which healthcare providers of medical imaging and imaging informatics professionals should be aware.